Postural correlates of pleasant landscapes visual perception - Akounach, Mbarka; Lelard, Thierry; Mouras, Harold (Frontiers in Psychology, 2025)
IntroductionThe interplay between motor skills and emotions in the brain represents a significant and longstanding research question. Recently, posturography has provided new insights into this subject. Understanding the biological processes that influence the appreciation of nature and landscapes is also a crucial concern, prompting various experimental methods and theoretical frameworks. This research aimed to propose, for the first time, the use of posturography to study the different ways postural control is modulated by visual perception of pleasant scenes.MethodsA total of 37 participants (27 females, 10 males; mean age = 24 years ±5 years) were shown images of pleasant and neutral landscapes, while posturographic data were collected. Two viewing conditions were employed: passive vision and active vision, where participants were instructed to envision themselves in the presented scenes.ResultsThe results indicated a differential modulation of the postural response based on valence factors (pleasant vs. neutral) and mental simulation (passive vs. active). Notably, significant differences in approach-avoidance behavior were observed approximately 7 s after the onset of stimulus viewing.DiscussionThe findings are discussed in relation to major theories in environmental psychology, highlighting the central role of emotional and embodiment processes in appreciating pleasant environmental scenes and related motor behaviors.